Cefoperazone rapidly and sensitive quantitative assessment via a validated RP-HPLC method for different dosage forms, in-use stability, and antimicrobial activities - Mostafa F. Al-Hakkani; Nourhan Ahmed; Alaa A. Abbas; Mohammad H. A. Hassan (BMC Chemistry, 2023)
Abstract Cefoperazone (Cfz) is a member of the third generation of parenteral cephalosporin antibiotics. It is used on a wide scale in prescribed antibiotic drugs as anti-infection, especially for Gram-negative and also against Gram-positive microorganisms. The current study aimed to find a rapid RP-HPLC method of Cfz analysis with high linearity, repeatability, sensitivity, selectivity, and inexpensive. In our developed method, there is no need to use special chemical reagents, a high percentage of organic solvent, a high flow rate, further guard column. The chromatographic system comprises an ODS column (150 mm × 4.6 mm × 5 μm). The mobile phase was prepared by mixing KH2PO4 solution: acetonitrile (80:20) with a flow rate of 1.0 mL/min at detection wavelength 230 nm, at room temperature using injection volume 20 μL. The method manifested a satisfied linearity regression R2 (0.9993) with a good repeatability range (0.34–0.92%) with LOD and LOQ; 4.04 μg/mL and 12.24 μg/mL respectively. The method proved its efficiency via system suitability achievement in the robustness and ruggedness conduction according to the validation guidelines. The shorter analysis time makes the method very valuable in quality control to quantify the commercial Cfz in pharmaceutical preparations. This improved HPLC method has been successfully applied for Cfz analysis for Peracef and Peractam vials in our routine finished and stability studies testing laboratories. Additionally, the detection limit of Cfz has been tested in our quality control lab to detect the smallest amount of traces that may be present after the cleaning process of the production machines for cephalosporins preparations. In a precedent for the first time, we were able to use the current analysis method to determine the minimum inhibitory concentration (MIC) and minimum bacteriostatic concentration (MBC). The conventional broth micro-dilution tube method was used to determine MIC at 250 µg/mL and MBC at 125 µg/mL of Cfz against the standard strain of Burkholderia cepacia (B. cepacia) ATCC 25416 as Gram-negative bacteria in vitro.